Taxonomic and genetic assessment of captive WhiteHanded Gibbons (Hylobates lar) in Peninsular Malaysia with implications towards conservation translocation and reintroduction programmes - MILLAWATI, GANI; Jeffrine Rovie, Ryan Japning; Frankie Thomas, Sitam; NOOR AZLEEN, MOHD KULAIMI; Chew Cheah, Zheng; Aida Nur Atiqah, -; Nur Maisarah, Abd Rahim; Ahmad Azhar, Mohammed (Pensoft Publishers, 2021)
Conservation translocation and reintroduction for the purpose of repopulating and reinforcing extirpated or depleted populations has been recognised as an important conservation tool, particularly for gibbon conservation in the immediate future. Feasibility assessments involving multiple factors, including taxonomic and genetic assessment of rescued and captive gibbons, are imperative prior to translocation and reintroduction programmes. In this study, we attempt to determine the subspecies and origin of captive Hylobates lar, White-handed gibbons, from Peninsular Malaysia to assist in future translocation and reintroduction programmes. A total of 12 captive and rescued H. lar samples were analysed using the control region segment of mitochondrial DNA. Sequence analyses and phylogenetic trees constructed using neighbour-joining, maximum likelihood, Bayesian inference, and network methods congruently differentiate all 12 captive individuals used in this study from other H. lar subspecies suggesting that these individuals belong to the H. lar lar subspecies. In addition, two populations of H. l. lar were observed: (1) a southern population consisting of all 12 individuals from Peninsular Malaysia, and (2) a possible northern population represented by three individuals (from previous studies), which might have originated from the region between the Isthmus of Kra, Surat Thani-Krabi depression, and Kangar-Pattani. Our findings suggest that the complete control region segment can be used to determine the subspecies and origin of captive H. lar.